ПРОИСХОЖДЕНИЕ СЛАВЯН. - АЛЕКСАХА, А.Г. (Гуманітарний журнал, 2012)
Эта книга представляет собой попытку реконструкции ранней истории славян со времени их выделения из индоевропейской общности до заверения их расселения. Для решения этой задачи автор также рассматривает некоторые проблемы расселения индоевропейцев. Для реконструкции ранней истории славян автор использовал предложенную иммодель развития общества.This book is an endeavor of reconstruction of early Slav history since time of their separation from Indo-European society to the end of their settling. For the solving of the problemauthor considered some problems of Indo-Europeans settling. For the reconstruction of early Slav history author applied proposed by himmodel of society development.
Keywords: славяне, индоевропейцы, пражская культура, прогрессология; Slavs, Indo-Europeans, Prague culture, progressology.